Ethnobotanical Study of Local Wisdom in the Utilization and Conservation of Medicinal Plants for Children's Health Around Mount Muria, Central Java - Wahidah, Baiq Farhatul; Husain, Fadly; Mulyanah, Wiwin; Khasanah, Rizkiati (Universitas Negeri Semarang, 2025)
Children of growing age are susceptible to various diseases because their immune systems are still developing. In many rural areas in Indonesia, including Colo Village, Mount Muria, people still use traditional medicine to treat diseases in children. This study documents the knowledge and conservation efforts of the Colo Village community regarding medicinal plants used to treat children's diseases. Data were collected qualitatively through semi-structured interviews with forty residents from four hamlets. The findings showed that the community used fifty-six plant species to treat various children's diseases. The results showed that the Colo Village community used 56 plant species to treat diseases in children, such as the Zingiberaceae family, such as turmeric (Curcuma domestica Val.), black ginger (Curcuma aeruginoasa Robx), ginger (Zingiber officinale Rosc.), and others. Diseases that can be treated are: cough, fever, worms, colds, mumps, diarrhea, mouth ulcers, loss of appetite, mouth ulcers, convulsions, and wounds. Plant organs utilized include leaves (45%), rhizomes (18%), fruits (14%), tubers (9%), seeds (7%), stems (3%), and flowers (4%). Drug processing is done by pounding (56%), boiling (11%), grating (24%), slicing (7%), and brewing (2%). Most plants are obtained through cultivation (55%), followed by obtaining from nature (29%) and purchasing at the market (16%). The Colo Village community preserves medicinal plants by cultivating them in their yards and gardens and utilizing other traditional methods. Strengthening ethnobotanical knowledge, especially among the younger generation, is key to maintaining local wisdom and biodiversity in this village.